2018
DOI: 10.1159/000493651
|View full text |Cite
|
Sign up to set email alerts
|

Genipin Reverses HFD-Induced Liver Damage and Inhibits UCP2-Mediated Pyroptosis in Mice

Abstract: Background/Aims: Liver damage is a typical manifestation of nonalcoholic fatty liver disease (NAFLD). It originates from excessive fat accumulation, leading to hepatocyte death, inflammation, and fibrosis. Nonalcoholic steatohepatitis (NASH) is a type of NAFLD with a prevalence of 49% in morbidly obese patients. Pyroptosis plays an important role in the development of NASH; thus, it is important to elucidate the effect of lipid accumulation on pyroptosis. Genipin (GNP), a natural water-soluble cross-linking ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…It has been reported that UCP2 reduces the ROS formation by preventing mitochondrial membrane hyperpolarization that in turn inhibits mitochondrial electron transport chain. Studies have shown that UCP2 confers protective effects on various stressors by decreasing mitochondrial ROS production in the brain and cardiomyocytes [26][27][28][29]. MnSOD is encoded by nuclear genome, synthesized in the cytosol, transported into the mitochondrial matrix post translationally via TOM and TIM23 complexes, and assembled into active enzyme with the incorporation of a manganese ion in the mitochondrial matrix.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that UCP2 reduces the ROS formation by preventing mitochondrial membrane hyperpolarization that in turn inhibits mitochondrial electron transport chain. Studies have shown that UCP2 confers protective effects on various stressors by decreasing mitochondrial ROS production in the brain and cardiomyocytes [26][27][28][29]. MnSOD is encoded by nuclear genome, synthesized in the cytosol, transported into the mitochondrial matrix post translationally via TOM and TIM23 complexes, and assembled into active enzyme with the incorporation of a manganese ion in the mitochondrial matrix.…”
Section: Discussionmentioning
confidence: 99%
“…UCP2 reduces the ROS formation by preventing mitochondrial membrane hyperpolarization that in turn inhibits mitochondrial electron transport chain. Studies have shown that UCP2 confers protective effects on various stressors by decreasing mitochondrial ROS production in the brain and liver 35 , 36 , 37 . It has also been reported that UCP2 could protect cardiomyocytes from exogenous oxidant stress 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GNP shows the choleretic effect by enhancing bilirubin disposal and augment of genes in charge of the efflux of a number of organic anions [ 45 ]. GNP widely implicates in the inhibition of uncoupling protein 2 (UCP2) in various experimental models of ROS generation [ 45 47 ]. This study demonstrated the protective effect of GNP against circadian disruption-induced damage of spermatogenesis and fertility in male mice.…”
Section: Discussionmentioning
confidence: 99%